2019
DOI: 10.3390/met9020196
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the High Tensile Ductility Improvement in an As-Solutionized AA7075 Alloy with the Aid of a Friction Stir Process

Abstract: The ductility enhancement of an AA7075 aluminum alloy aided by a friction stir process (FSP) and various heat treatments was investigated and compared in terms of outcome with full annealing (O). The results indicate that a big improvement in the tensile ductility was achieved by freezing the sample at temperatures below 0 °C after the solution treatment and water quenching (W treatment), and further improvement could be acquired via a friction stir process due to grain refinement (<6 μm). Thus, the observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Even after heat treatment at 200 °C for 240 min, the IR-heated specimen showed a better Young's modulus than that of the RH-heated specimen. In the XRD patterns (shown in Figure 13), according to our previous research [11], MgZn2 and Al-Cu(Cr)Fe compounds could be observed. Comparing RA60-120-12H_200-4H and IA60-120-12H_200-4H specimens, RA60-120-12H_200-4H has a more obvious MgZn2 peak compared to that for IA60-120-12H_200-4H.…”
Section: High-temperature Resistancesupporting
confidence: 58%
See 1 more Smart Citation
“…Even after heat treatment at 200 °C for 240 min, the IR-heated specimen showed a better Young's modulus than that of the RH-heated specimen. In the XRD patterns (shown in Figure 13), according to our previous research [11], MgZn2 and Al-Cu(Cr)Fe compounds could be observed. Comparing RA60-120-12H_200-4H and IA60-120-12H_200-4H specimens, RA60-120-12H_200-4H has a more obvious MgZn2 peak compared to that for IA60-120-12H_200-4H.…”
Section: High-temperature Resistancesupporting
confidence: 58%
“…The heating rate of the IR heating furnace has been published in our previous research [7]. Conventional artificial aging parameters [10,11] were utilized to establish baseline information (i.e., solution heat treatment conditions: RH/480 • C_60 min, aging conditions: RH/120 • C_24 h). The heat treatment conditions are shown in Tables 2 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…In closing, the present research provides an alternative means to control the PLC phenomenon via the addition of a nanocomposite material to an Al-Mg alloy while concurrently offering a means to analyze and quantify the serrated flow. With the increasing application of new joining technologies for aluminum, including friction stir processing [29,30] and alternative welding materials [31], the manifestation of PLC in the base metal, the heat affected zone, or the weld requires control. In this context, the present work proposes an appealing approach to counteract DSA upon such fabrication processes using an Al/NbB 2 nanocomposite.…”
Section: Statistical Analysis Of the Plc Phenomenonmentioning
confidence: 99%